Sowing the seeds of conflict? Low income housing delivery, community participation and inclusive citizenship in South Africa. (October 2016) - Patel, Kamna
The delivery of housing to low income citizens across South Africa reflects the state's realisation of citizens' social rights to housing and can help to strengthen a citizen's sense of belonging. Additionally, through the very processes of housing delivery, such as decentralised mechanisms with strong community participation, principles of inclusive citizenship are forged and enacted. However, it is argued in this paper that because housing allocation is devolved and power granted to local elites, an important aspect of citizenship-making has also been devolved with insufficient checks and balances. The paper cautions that the decision-making of local elites who determine access to housing and thus the realisation of citizenship rights, is mitigated by their subjectivities. Based on case studies of selected settlements in eThekwini (Durban), the paper examines how residents access housing in slum upgrade programmes. It finds that, beyond national eligibility criteria additional localised criteria are evident which demand that residents use their identity and social relationships to both provide evidence of their eligibility and negotiate access. The paper further cautions that these local processes may be sowing seeds of conflict by propagating existing social tensions, particularly around ethno- and xenophobia, and party political contests. Such conflict ultimately undermines citizenship ideals.